Giant Cell Tumor of Hoffa’s Fat Pad: A Case Report - Rupesh Kumar Vaidya; Prabal Pradhan; Karishma Malla Vaidya (Journal of Nepal Medical Association)
Tenosynovial giant cell tumor (GCT) is a rare, benign disorder involving the joint’s synovial lining, tendon sheath or bursa. It can be classified as localized or diffuse based on its pattern and behavior. Localized form is extremely rare in knee joint. We present an unusual case of localized form of GCT in Hoffa’s fat pad in a young female, treated with arthroscopic resection and monitored for over a year with no recurrence. Despite its rarity, GCT of Hoffa’s fat pad should be considered in cases of non-traumatic knee pain.